Long-range magnetic coupling across a polar insulating layer - W. M. Lü (Nature Portfolio, 2016)
Magnetic interactions in solids are usually short-range or else they involve itinerant electrons. Here, the authors evidence a long-range magnetic coupling mediated by orbital moments in a polar spacer layer of nonmagnetic insulating oxide, with a sign which oscillates with spacer thickness.